An Experimental 10-Port Microwave System for Brain Stroke Diagnosis-Potentials and Limitations - Pokorny, Tomas; Redr, Jan; Laierova, Hana; Smahelova, Barbora; Kollar, Jakub (Sensors (Basel, Switzerland), 2025)
Microwave imaging systems show potential as replacements for commonly used stroke diagnostic systems. We developed and tested a 10-port microwave system on a liquid head phantom with ischemic and hemorrhagic strokes of varying sizes and positions. This system allows for visualization of changes in dielectric parameters using the TSVD Born approximation, enabling recognition of stroke position and size from the resulting images. The SVM algorithm effectively distinguishes between ischemic and hemorrhagic strokes, achieving 98% accuracy on experimental data, with 99% accuracy in ischemic scenarios and 97% in hemorrhagic scenarios. Using the TSVD Born algorithm, it was possible to precisely image changes in the absolute permittivity of different stroke locations; however, changes in stroke size were more apparent in the variations of absolute permittivity than in the reconstructed stroke size within the antenna plane. Outside this plane, changes in the S-parameters decreased depending on the distance and size of the stroke, making detection and classification more difficult. One ring of antennas around the head proved insufficient, prompting us to focus on developing a system with antennas positioned around the entire head.
Keywords: algoritmy; brain stroke; cévní mozková příhoda; mozek; mikrovlnné zobrazování; Humans; fantomy radiodiagnostické; lidé; Algorithms; Phantoms, Imaging; Microwave Imaging; Brain; SVM; mikrovlny; TSVD Born approximation; Microwaves; Stroke; microwave devices